2019
DOI: 10.1038/s41436-018-0015-7
|View full text |Cite|
|
Sign up to set email alerts
|

A homozygous FANCM frameshift pathogenic variant causes male infertility

Abstract: These findings revealed male infertility to be a novel phenotype of human patients with a biallelic FANCM PV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 36 publications
6
66
1
1
Order By: Relevance
“…P-value 0.824 0.587 0.120 0.247 0.026 1 Processed red meat included sausages and bologna 2 Red meat included hamburger, beef and lamb meat as a mixed or main dish 3 Poultry included chicken with or without skin, as a main dish, sandwich, or frozen dinner 4 Organ meat included liver and chicken liver…”
Section: Competing Interestsmentioning
confidence: 99%
“…P-value 0.824 0.587 0.120 0.247 0.026 1 Processed red meat included sausages and bologna 2 Red meat included hamburger, beef and lamb meat as a mixed or main dish 3 Poultry included chicken with or without skin, as a main dish, sandwich, or frozen dinner 4 Organ meat included liver and chicken liver…”
Section: Competing Interestsmentioning
confidence: 99%
“…The screening for candidate pathogenic variants was performed as we previously described [24]. The annotation and filtration of identified variants were based on Ensembl (http://www.ensembl.org).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that chromosomal aberrations and Y chromosome microdeletions are frequent genetic causes of SO; however, routine screening for these well‐established genetic causes only results in the diagnosis of a small number of cases. Recently, although several mutations in spermatogenesis‐related genes, including KLHL10 , CDC14A , and FANCM , have been reported to cause oligozoospermia or SO in humans, fewer than 25% of SO cases currently have a clear genetic diagnosis. Considering the complex process of spermiogenesis and large number of genes involved, it can be presumed that most genetic causes of SO have not been characterized.…”
Section: Introductionmentioning
confidence: 99%